The Effect of Customer Experience and Omnichannel Integration on Customer Loyalty through Customer Engagement and Customer Satisfaction as Mediation - Dewantara, Hendra; Laulita, Nasar Buntu (Jurnal Bisnis dan Manajemen, 2024)
This study aims to measure the impact of customer experience and channel integration on customer loyalty, with customer engagement and satisfaction as mediation variabel in omnichannel context on customers who buy fashion products through websites. The research method used is Structural Equation Modeling (SEM) Analysis using SmartPLS. This research is quantitative with purposive sampling method, involving 280 samples. At the end of the research period, 331 responses from users of the omnichannel online shopping system on the website were obtained to be analyzed. The results of the analysis show that customer experience and channel integration significantly positively affect customer engagement, satisfaction, and loyalty, so this hypothesis is accepted. In addition, customer engagement and satisfaction mediate the relationship between customer experience and channel integration with customer loyalty, so this hypothesis is also accepted.